2006
DOI: 10.1242/dev.02641
|View full text |Cite
|
Sign up to set email alerts
|

Two separate molecular systems, Dachsous/Fat and Starry night/Frizzled,act independently to confer planar cell polarity

Abstract: Planar polarity is a fundamental property of epithelia in animals and plants. In Drosophila it depends on at least two sets of genes: one set, the Ds system, encodes the cadherins Dachsous (Ds) and Fat (Ft), as well as the Golgi protein Four-jointed. The other set, the Stan system, encodes Starry night (Stan or Flamingo) and Frizzled. The prevailing view is that the Ds system acts via the Stan system to orient cells. However, using the Drosophila abdomen, we find instead that the two systems operate independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
444
4
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(475 citation statements)
references
References 45 publications
25
444
4
1
Order By: Relevance
“…Most of the A cells make cuticular hairs or bristles that point posteriorly. As shown in Figure 3B (Casal et al, 2006), a gradient of Ds increases from anterior to posterior, while there is an opposing gradient of Fj. Although there is no gradient of Ft proteins, there should be a gradient of Ft activity, driven by the action of Fj on Ft.…”
Section: Developmental Dynamicsmentioning
confidence: 83%
See 2 more Smart Citations
“…Most of the A cells make cuticular hairs or bristles that point posteriorly. As shown in Figure 3B (Casal et al, 2006), a gradient of Ds increases from anterior to posterior, while there is an opposing gradient of Fj. Although there is no gradient of Ft proteins, there should be a gradient of Ft activity, driven by the action of Fj on Ft.…”
Section: Developmental Dynamicsmentioning
confidence: 83%
“…The bottom row shows putative distributions of Ds (blue) and Ft (red). There is a gradient of Ds increasing from anterior to posterior, and of opposing gradients of Fj and Ft activity (Casal et al, 2006), as indicated by the size of the letters. Although there is no gradient of Ft protein, a gradient of Ft activity is speculated, driven by the action of Fj on Ft. Only those molecules of Ft and Ds that form trans-heterodimers are shown; free Ft and Ds, as well as other possible forms of Ds and Ft (e.g., cis-complexes), are not shown, even though they may be in excess (the Ds protein gradient peaks posteriorly, but the gradient of Ds molecules engaged in trans-heterodimers peaks anteriorly).…”
Section: Involvement Of the Ds-ft Signaling System In Planar Cell Polmentioning
confidence: 99%
See 1 more Smart Citation
“…UAS-DsFL [18] comprises the complete coding region of full-length Ds [17]. UAS-ectoDs encodes a large extracellular domain anchored to the cell membrane [15]. The UAS-DsIntraV5 transgene was generated by fusion of the cDNA sequence (nt 10 153 to 11 464; Genbank: L08811.2) and one copy of the V5 epitope to the C-terminus (Ct) in the pUAS-T vector.…”
Section: Drosophila Geneticsmentioning
confidence: 99%
“…Reported data provide genetic evidence that Ds can regulate these processes in two different ways: in a cell-autonomous or a non-cell-autonomous manner. Therefore, PCP and growth can be also regulated by Ds independently of Ft [7,8,14,15]. At present it is difficult to envision how the current model, based on the requirement of the extracellular domain of Ds, can explain the cell-autonomous function.…”
Section: Introductionmentioning
confidence: 99%